2006
DOI: 10.1074/jbc.m605611200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Rearrangements of Sucrose Phosphorylase from Bifidobacterium adolescentis during Sucrose Conversion

Abstract: The reaction mechanism of sucrose phosphorylase from Bifidobacterium adolescentis (BiSP) was studied by site-directed mutagenesis and x-ray crystallography. An inactive mutant of BiSP (E232Q) was co-crystallized with sucrose. The structure revealed a substrate-binding mode comparable with that seen in other related sucrose-acting enzymes. Wild-type BiSP was also crystallized in the presence of sucrose. In the dimeric structure, a covalent glucosyl intermediate was formed in one molecule of the BiSP dimer, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 20 publications
6
113
0
Order By: Relevance
“…The sequence motif DAxxY/F (corresponding to Asp223-Tyr227 of HBG-III) frequently occurs in GH-13 enzymes belonging to subfamilies 4 (sucrose hydrolases), 16 (trehalose synthases), 17 (-glucosidases), 18 (sucrose phosphorylases), and 23 (-glucosidases). The protein structures of Tyr-harboring enzymes, sucrose hydrolase derived from Xanthomonas campestris 27) and sucrose phosphorylase from Bifidobacterium adolescentis, 28) indicate that the side chain of Tyr has no direct contact with a fructose moiety of sucrose. It is accommodated on the far side of the pocket from the equivalent residues, 27) as observed for the isomaltotriose-binding mode of dextran glucosidase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sequence motif DAxxY/F (corresponding to Asp223-Tyr227 of HBG-III) frequently occurs in GH-13 enzymes belonging to subfamilies 4 (sucrose hydrolases), 16 (trehalose synthases), 17 (-glucosidases), 18 (sucrose phosphorylases), and 23 (-glucosidases). The protein structures of Tyr-harboring enzymes, sucrose hydrolase derived from Xanthomonas campestris 27) and sucrose phosphorylase from Bifidobacterium adolescentis, 28) indicate that the side chain of Tyr has no direct contact with a fructose moiety of sucrose. It is accommodated on the far side of the pocket from the equivalent residues, 27) as observed for the isomaltotriose-binding mode of dextran glucosidase.…”
Section: Discussionmentioning
confidence: 99%
“…1) is often found in subfamilies 1,2,5,15,17,19,24,27,28,31,32, and 36, which include -1,4-linkage-specific enzymes such as -amylases, cyclomaltodextrin glucanotransferases, and -glucosidases. Most -amylases and cyclomaltodextrin glucanotransferases have dipeptide Lys-His at the C-terminal end of the motif.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results support the hypothesis that the undissociated OH form of benzoic acid can be used as an effective acceptor molecule by the enzymes. This is quite reasonable from the view point of the proposed catalytic mechanism of phosphorolysis by sucrose phosphorylase from Bifidobacterium adolescentis that protonated phosphate group is necessary for binding to the catalytic domain of the enzyme (Mirza et al 2006). The transfer efficiency of the transglycosylation reaction of sucrose phosphorylase from L. mesenteroides was much lower than that of sucrose phosphorylase from S. mutans at pH 3.9.…”
Section: Glycosylation Of Benzoic Acid By Sucrose Phosphorylasementioning
confidence: 72%
“…This is quite reasonable from the viewpoint of the proposed catalytic mechanism of the transglycosylation reaction toward phosphate by sucrose phosphorylase from Bifidobacterium adolescentis. 25) It suggested that sucrose phosphorylase can react with HPO4 2 or H2PO4 but not with PO4 3 because a protonated phosphate group is necessary for its binding to the catalytic domain of the enzyme. We considered that the glucosyltransfer reaction of sucrose phosphorylase was very slow around neutral pH, since the reaction mixture contained only a small amount of the available form of acetic acid.…”
Section: Improvement Of Acidic Taste Of Acetic Acid By Glucosylationmentioning
confidence: 99%